AB1167 Antinuclear Antibodies in Rheumatoid Arthritis: Predictors of Response to Anti-TNF Alpha Treatment?. (9th June 2015) - Fonseca, R.; Vieira, R.; Madureira, P.; Rosa-Gonçalves, D.; Aguiar, F.; Rocha, T.; Bernardo, A.; Mariz, E.; Bernardes, M.; Costa, L.
Abstract : Background: Among rheumatoid arthritis (RA) patients, the influence of antinuclear antibodies (ANA) in clinical response to anti-TNFα treatment has been suggested. However, recent studies showed conflicting results. Objectives: To determine the impact of positivity for ANA at baseline in clinical response and persistency of anti-TNFα treatment in RA patients. Methods: Observational retrospective cohort study was performed. Patients fulfilling American College of Rheumatology criteria for RA, who started their first anti-TNFα between 2002 and 2013, and had baseline ANA determination, were included. Disease activity (assessed by DAS28) was measure at baseline, 6, 12, 18 and 24 months (M). Clinical response was evaluated by EULAR criteria and three categories of response were defined: good, mild and no response. Two groups were compared: baseline ANA positive (cut-off titter >1/100) and ANA negative patients. Statistical analyses were performed using t-test, Mann-Whitney U-test and Chi-square. The period of observation for evaluating drug survival was defined as the time between starting anti-TNFα and their discontinuation. Kaplan-Meier survival analysis was used to assess persistence, log rank tests were used to compare drug survival between the two groups (SPSS 21.0). Results: 74 patients were included. 90% were female (n=65) with a mean age of 54.56 years (SD ±10.57). 27.4% (20) patients were ANA positive at baseline. 6.8% (5) patients started infliximab, 38.4% (28) etanercept, 42.5% (31) adalimumab and 12.3% (9) golimumab. At baseline, no statistically significant differences were found between the two groups in age, disease duration, concomitant use of methotrexate, DAS28 and TNFα inhibitor. EULAR response at 6M differed significantly between the two groups. Good, moderate, and no response were 8.3%, 33.3%, and 58.4% in baseline ANA positive patients versus 11.9%, 69.1% and 19% in ANA negative patients, respectively p=0.027). No difference was found in clinical response at 12, 18 or 24M. No significant differences were found in discontinuation rate due to all causes, side effects and non-effectiveness. However, ANA positive patients showed a tendency to present with a higher switch rate (45% versus 27.5%, p=0.128). Survival of the first anti-TNF-α agent was lower in ANA positive patients at baseline (55%) than in ANA negative patients (72.5%) and separation of survival curves had statistically significance (log-rank 5.8, p=0.016). Conclusions: Our study suggests a poorer clinical response in the first 6 months of anti-TNFα therapy in baseline ANA positive patients. Despite failing to stablish a statistically significant difference in discontinuation rate between ANA positive/negative patients, it is suggested that ANA positive patients have a higher switch rate and a lower anti-TNFα agent survival. Disclosure of Interest: None declared